Corona discharge in atmospheric pressure air under a modulated voltage pulse of 10 ms; Atmospheric and Oceanic Optics; Vol. 26, iss. 5 - Rybka D. V.; Andronikov I. V.; Evtushenko G. S. Gennady Sergeevich; Kozyrev A. V.; Kozhevnikov V. Yu.; Kostyrya I. D.; Tarasenko V. F. Victor Fedotovich; Trigub M. V. Maksim Viktorovich; Shutko Yu. V. (2013, 2013)
Title screen